PENYELESAIAN KREDIT BERMASALAH MELALUI KEBIJAKAN HAPUS BUKU DAN HAPUS TAGIH PADA BANK PEMERINTAH DAN BANK SWASTA (Studi di PT. Bank Sumut,Tbk dan PT. Bank Mega Syariah,Tbk) - FADILLAH FATAH NASUTION (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Tan Kamello, SH, MS2. Prof. Dr. Saidin, SH, MHum3. Dr. Dedi Harianto, SH, MHumEvery loan problem which is failed in rescheduling, reconditioning, restructuring, and collateral confiscation will cause NPL (non-performing loan). Bank management, either the government banks or private banks, can make a policy on wipe-off the books and wipe-off the bills toward NPL as an attempt to decrease it which influences bank health. The research problems are how about determining the criteria of clients whose books and bills can be wiped-off, how about the mechanism of the implementation of wipe-off the books and wipe-off the bills in government banks or private banks, and how about the legal consequence of this policy.The result of the research showed that the implementation of wipe-off the books and wipe-off the bills at PT. Bank Sumut, Tbk and PT. Bank Mega Syariah, Tbk should be in accordance with PBI No. 14/15/PBI/2012 as general requirements and special requirements of each banks as an internal policy such as force majeur, debtors are bancrupt, or debtors flee. The mecanism of wiping-off the credit in government banks used to be through PUPN, but now it is through the mechanism of cooperatives, based on the approval of the Directors through each internal policy, including private banks. The legal consequence of this policy is the decrease in earnings, the increase in employees work load to bill, and the increase in clients who are in the blacklist of Bank Indonesia (BI) which influence its image in the world’s banks.Keyword : Hapus Buku, Hapus Tagih, Kredit Macet